Conditioned medium of engineering macrophages combined with soluble microneedles promote diabetic wound healing - Hongyu Wang; BaoHua Wei; Hasi WuLan; Bin Qu; Huilong Li; Jing Ren; Yan Han; LingLi Guo (PLoS ONE, 2025)
Diabetic wounds have a profound effect on both the physical and psychological health of patients, highlighting the urgent necessity for novel treatment strategies and materials. Macrophages are vital contributors to tissue repair mechanisms. Macrophage conditioned medium contains various proteins and cytokines related to wound healing, indicating its potential to improve recovery from diabetic wound. Engineering macrophages may enable a further improvement in their tissue repair capacity. Fibroblast growth factor 2 (FGF2) is a crucial growth factor that plays an integral role in wound healing process. And in this study, a stable macrophage cell line (engineered macrophages) overexpressing FGF2 was successfully established by engineering modification of macrophages. Proteomic analysis indicated that conditioned medium derived from FGF2 overexpressed macrophages may promote wound healing by enhancing the level of vascularization. Additionally, cellular assays demonstrated that this conditioned medium promotes endothelial cell migration in vitro. For the convenience of drug delivery and wound application, we prepared soluble hyaluronic acid microneedles to load the conditioned medium. These soluble microneedles exhibited excellent mechanical properties and biocompatibility while effectively releasing their contents in vivo. The microneedles significantly accelerated wound healing, leading to a marked increase in vascular proliferation and improved collagen deposition within a full thickness skin defect diabetic mouse model. In summary, we developed a type of hyaluronic acid microneedle loaded with conditioned medium of engineered macrophages. These microneedles have been demonstrated to enhance tissue vascularization and facilitate diabetic wound healing. This might potentially serve as a highly promising therapeutic approach for diabetic wounds.